PSYCHOLOGY-PEDAGOGICAL CULTURE AS THE COMPOSITION OF ACADEMIC CULTURE OF THE TEACHER OF HIGH SCHOOL - Прудніков, О. В.; Василюк, С. М.; Гуцуляк, А. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article analyzes the essence of the psychological and pedagogical culture of the teacher. It is proved that a high level of academic culture of a teacher of higher education in Ukraine is possible only subject to compulsory psychological and pedagogical preparedness.